Weak and periodical solutions of the navier-stokes equation in noncylindrical domains - Quiroga Gonzáles, Cruz Sonia; Limaco, Juan; Gamboa, Pedro; Barreto, Rioco K. (Pontificia Universidad Católica del Perú, 2001)
We consider the Navier Stokes equation in noncylindrical domain and prove the existence of weak and periodical solutions.
Keywords: Navier-Stokes; Noncylindrical Domains; Weak And Periodical Solutions; Matemáticas; https://purl.org/pe-repo/ocde/ford#1.01.00